ANALISIS MODEL PEMBERDAYAAN EKONOMI MUALAF PADA LEMBAGA BAITUL MAL PROVINSI ACEH - Fil Amzatil Akbar; Nurma Sari; eka - nurlina; Rusdi Rusdi (universitas teuku umar, 2021)
This study aims to describe the empowerment program of mualaf (convert) at the Baitul Mal Aceh, Indonesia. The case study using a qualitative descriptive approach, data were collected through interviews with the head of the field of collection in Baitul Mal Aceh, mualaf, stakeholders and direct participatory observation and documentation. In validating data, this study uses data triangulation techniques before being analyzed through data reduction and conclusions. The results of this study indicate that the empowerment program implemented by Baitul Mal Aceh through its work programs has a role and influence in the empowerment of mualaf in Aceh. Muslim converts have a good relationship with neighbors and have been able to meet the needs of daily life. Not only empowered economically, converts also experience an increase in spiritual terms.